Pengaruh Profitabilitas dan Solvabilitas terhadap Return Saham pada Sub Sektor Makanan dan Minuman: Studi Empiris di Bursa Efek Indonesia Tahun 2020 – 2022 - Andi Febri Andra; Suyatmin Waskito Adi (VISA: Journal of Vision and Ideas, 2024)
This study aims to empirically examine the effect of Profitability (ROE) and Solvency (DER) both partially and simultaneously on Stock Returns. The research was conducted on food and beverage sector companies listed on the Indonesia Stock Exchange in 2020-2022 using a period per year. The samples used in this study amounted to 21 food and beverage companies. Where the sample selection was carried out using purposive sampling method. The type of data used in this study is quantitative research where the data used is secondary data. Secondary data is data obtained indirectly but obtained through published intermediary media. Secondary data in the research in this study comes from annual financial reports. The data analysis technique used in this research is multiple linear regression. Based on the results of data processing, it shows that partially Profitability proxied by Return On Equity (ROE) has a significant positive effect while Solvency proxied by Debt to Equity Ratio (DER) has an insignificant negative effect on stock returns.